Current Understanding of Long-Term Cognitive Impairment After Sepsis - Li, Ying; Ji, Muhuo; Yang, Jianjun (Frontiers in Immunology, 2022)
Sepsis is recognized as a life-threatening multi-organ dysfunction resulting from a dysregulated host response to infection. Although the incidence and mortality of sepsis decreases significantly due to timely implementation of anti-infective and support therapies, accumulating evidence suggests that a great proportion of survivors suffer from long-term cognitive impairment after hospital discharge, leading to decreased life quality and substantial caregiving burdens for family members. Several mechanisms have been proposed for long-term cognitive impairment after sepsis, which are not mutually exclusive, including blood brain barrier disruption, neuroinflammation, neurotransmitter dysfunction and neuronal loss. Targeting these critical processes might be effective in preventing and treating long-term cognitive impairment. However, future in-depth studies are required to facilitate preventive and/or treatment strategies for long-term cognitive impairment after sepsis.